Feminization of complex traits in Drosophila melanogaster via female‐limited X chromosome evolution. (1st December 2020) - Lund‐Hansen, Katrine K.; Abbott, Jessica K.; Morrow, Edward H.
Abstract: A handful of studies have investigated sexually antagonistic constraints on achieving sex‐specific fitness optima, although exclusively through male‐genome‐limited evolution experiments. In this article, we established a female‐limited X chromosome evolution experiment, where we used an X chromosome balancer to enforce the inheritance of the X through the matriline, thus removing exposure to male selective constraints. This approach eliminates the effects of sexually antagonistic selection on the X chromosome, permitting evolution toward a single sex‐specific optimum. After multiple generations of selection, we found strong evidence that body size and development time had moved toward a female‐specific optimum, whereas reproductive fitness and locomotion activity remained unchanged. The changes in body size and development time are consistent with previous results, and suggest that the X chromosome is enriched for sexually antagonistic genetic variation controlling these particular traits. The lack of change in reproductive fitness and locomotion activity could be due to a number of mutually nonexclusive explanations, including a lack of sexually antagonistic variance on the X chromosome for those traits or confounding effects of the use of the balancer chromosome. This study is the first to employ female‐genome‐limited selection and adds to the understanding of the complexity of sexually antagonistic genetic variation.